The application of fault signature analysis in Tenaga Nasional Berhad Malaysia - Zin, Abdullah Asuhaimi M.; Karim, S. P. A. (Institute of Electrical and Electronics Engineers, 2007)
Unplanned electrical power outages are a major concern to power utilities throughout the whole world. Unfortunately, power outages will continue to occur and they cannot be fully prevented. It could be the result of lightning strikes, tree encroachment, or equipment failure. However, the impact can be reduced if power system operators are equipped with the appropriate tools to analyze the root cause of the failure. Without sufficient tools to identify the nature of a fault, the restoration process could be delayed because the operator does not know whether it is safe to normalize the isolated line. This paper describes the new and simplified fault signature analysis approach on Tenaga Nasional Berhad using a digital fault recorder. The research focuses on the contribution of the lightning strike and tree encroachment to the overhead line tripping in Malaysia